2018
DOI: 10.3390/w10030302
|View full text |Cite
|
Sign up to set email alerts
|

Water Temperature, pH, and Road Salt Impacts on the Fluvial Erosion of Cohesive Streambanks

Abstract: Increasing human populations and global climate change will severely stress our water resources. One potential unforeseen consequence of these stressors is accelerated stream channel erosion due to increased stream temperatures and changes in stream chemistry, which affect the surface potential and hence the stability of soil colloids. The objectives of this study were to determine the effect of water temperature, pH, and salinity on streambank erosion rates; determine how erosion rates vary with clay mineralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
(40 reference statements)
0
18
0
1
Order By: Relevance
“…In addition to reducing variability in the erosion rates resulting from slight differences in the hydraulic shear stress, this normalization also created nondimensional erosion rates. Shear velocity ( u *) values were determined by fitting velocity profile data in the log‐law region to the rough “law of the wall” equation given below (Hoomehr et al, 2018): Uu*=1kln(yy0) where U is the streamwise velocity at a distance ( y ) from the soil surface, u * is the shear velocity, k is the von Karman constant (0.4), and y 0 is the roughness height.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to reducing variability in the erosion rates resulting from slight differences in the hydraulic shear stress, this normalization also created nondimensional erosion rates. Shear velocity ( u *) values were determined by fitting velocity profile data in the log‐law region to the rough “law of the wall” equation given below (Hoomehr et al, 2018): Uu*=1kln(yy0) where U is the streamwise velocity at a distance ( y ) from the soil surface, u * is the shear velocity, k is the von Karman constant (0.4), and y 0 is the roughness height.…”
Section: Methodsmentioning
confidence: 99%
“…It is also possible to have elevated streambank temperatures relative to that of the stream flow since the loss of riparian shade and the presence of urban infrastructure such as pipelines and utility lines, as well as modern technologies such as bridge deck deicing systems using thermal energy sources, can result in localized elevated soil temperatures. Water temperature was shown to be positively correlated with the fluvial entrainment of remolded cohesive soils (Hoomehr et al, 2018). Although previous research has shown the importance of the physicochemical properties of soil and water on cohesive soil erosion (Grissinger, 1966; Partheniades and Paaswell, 1970; Sargunam et al, 1973; Arulanandan et al, 1975), the effect of water temperature on cohesive soil erosion has not been fully explored, while the effect of soil temperature on erosion is largely unknown.…”
Section: Sediment Properties and Processes That Affect Soil Erodibilimentioning
confidence: 99%
“…The research articles included in this special issue specifically targeted three areas that are key to better understanding streambank erosion and failure, namely, monitoring [8][9][10][11], modeling [12][13][14][15][16][17], and management [18][19][20][21]. As an ensemble, the articles highlight the value of monitoring campaigns to characterize the effect of external drivers (e.g., hydrologic events), the capabilities and limitations of numerical models for predicting the response of the system (e.g., stream restoration design), and the effectiveness of management practices to prevent and mitigate the impacts of streambank erosion and failure.…”
Section: Main Outcomes Of the Special Issuementioning
confidence: 99%
“…Their results emphasize the importance of selecting an adequate stabilization technique to manage bank erosion, while considering the associated cost and performance under extreme conditions. Hoomehr et al [21] carried out flume experiments to study the effect of water temperature, pH, and salinity on bank erosion rates. Their results indicate that erosion rates are affected by water temperature, with higher rates as temperature rises.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation